The radiology workforce's response to the COVID-19 pandemic in the Middle East, North Africa and India. Issue 2 (May 2021) - Elshami, W.; Akudjedu, T.N.; Abuzaid, M.; David, L.R.; Tekin, H.O.; Cavli, B.; Issa, B.
Abstract: Introduction: This study aimed to investigate the response of the radiology workforce to the impact of the coronavirus disease 2019 (COVID-19) pandemic on professional practice in India and eight other Middle Eastern and North African countries. It further investigated the levels of fear and anxiety among this workforce during the pandemic. Methods: A quantitative cross-sectional study was conducted using an online survey from 22 May-2 June 2020 among radiology workers employed during the COVID-19 pandemic. The survey collected information related to the following themes: (1) demographic characteristics, (2) the impact of COVID-19 on radiology practice, and (3) fear and (4) anxiety emanating from the global pandemic. Results: We received 903 responses. Fifty-eight percent had completed training on infection control required for handling COVID-19 patients. A large proportion (79.5%) of the respondents strongly agreed or agreed that personal protective equipment (PPE) was adequately available at work during the pandemic. The respondents reported experiences of work-related stress (42.9%), high COVID-19 fear score (83.3%) and anxiety (10%) during the study period. Conclusion: There was a perceived workload increase in general x-ray and Computed Tomography imaging procedures because they were the key modalities for the initial and follow-up investigations of COVID-19. However, there was adequate availability of PPE during the study period. Most radiology workers were afraid of being infected with the virus. Fear was predominant among workers younger than 30 years of age and also in temporary staff. Anxiety occurred completely independent of gender, age, experience, country, place of work, and work status. Implications for practice: It is important to provide training and regular mental health support and evaluations for healthcare professionals, including radiology workers, during similar future pandemics.